The benefits of a United Nations Standing Army: Using Article 43 of the UN Charter to improve international human rights and peace - Chigona, Thandizo (Department of Public Law, 2025)
The purpose of the United Nations (UN) as set in the UN Charter is to protect the ‘people' of the world and provide the necessary freedoms and security for them to flourish in their own ways. This has been expressed through the UN Charter's various chapters and articles that have been brought into practical effect by the UN's institutional and administrative bodies such as the General Assembly and the Security Council. Despite this, the world continues to witness humanitarian crises flaring up at consistent (if not growing) levels, and in most cases these humanitarian crisis situations occur in conflict zones. In attempts to curb this, the UN had initiated several peacekeeping missions, some of which had success in the early stages of the organization's peacekeeping agenda. However, the broader failure of these peacekeeping operations is mainly attributed to the disorganized and decentralized nature of current UN peacekeeping operations. These failings lead to perpetual cycles of mistrust/dissatisfaction which result in reduced support by states which then precipitates further failures and this again fuels the mistrust and dissatisfaction of member states and the public opinion. However, an organized standing army under the UN would arguably do far better at ensuring the protection of human rights across the world. Based off the cohesive and structured nature of a standing army, a UN army would likely find far more success in promoting international peace and security than current methods of peacekeeping or awaiting approval for collective action from the Security Council. The structure to allow such a force already exists within the UN charter, most notably under article 43. However, there are other far-reaching avenues to achieve this which are explored in this study. Ultimately, a UN Standing army would improve international peace and security as well as increase the protection of human rights.